Genetic and Environmental Risks for High Blood Pressure Among African American Mothers and Daughters - Taylor, Jacquelyn Y. (2009)
OBJECTIVE: To determine the relationship between genetic and environmental lifestyle factors (physical activity and sodium) on blood pressure (BP) among African-American women. METHOD: In this cross-sectional study involving 108 African-American mothers and daughters from a Midwestern area, investigators obtained BP measurements, information on minutes of physical activity, amount of sodium intake, and buccal swab saliva samples. RESULTS: Of the 4 single nucleotide polymorphisms (SNPs) on the sodium bicarbonate cotransporter gene (SLC4A5), rs8179526 had a statistically significant interaction with cytosine/thymine (C/T) genotype by sodium status on systolic BP (SBP; p = .0077). For gene × physical activity interaction, 2 significant interactions (cytosine/adenine [C/A] genotype by physical activity and adenine/adenine [A/A] genotype by physical activity, p = .0107 and p = .0171, respectively) on SBP and 1 on diastolic BP (DBP; A/A genotype by physical activity, p = .0233) were found on rs1017783. Two significant guanine/adenine [G/A] genotype by physical activity interactions were found on rs6731545 for SBP and DBP (p= .0160 and p= .0492, respectively). DISCUSSION: A gene × environmental interaction with rs8179526 has a protective effect on SBP in African-American women with high sodium intake. Participants with C/T genotype of rs8179526 who consumed greater than 2,300 mg of sodium had lower SBP than those who consumed less than recommended. Women with thymine/thymine (T/T) genotype of rs8179526 who consumed greater than 2,300 mg had lower SBP than those who consumed less. Awareness of both the protective and deleterious properties of rs8179526 in African-American women may one day assist in determining appropriate treatment plans.